Voluntary vs Compulsory Playing Contexts: Motivational, Cognitive, and Game Experience Effects. (February 2017) - Rodríguez-Aflecht, Gabriela; Hannula-Sormunen, Minna; McMullen, Jake; Jaakkola, Tomi; Lehtinen, Erno
Background . Serious games are often used in formal school contexts, in which students' lack of control over the playing situation may have repercussions on any motivational gains. Aims and Method . The first aim was to investigate to what extent n = 579 fifth grade students in Mexico who received a mathematics serious game played it voluntarily. Then, we explored how students who played voluntarily ( n = 337) differed from those who did not by either gender or pre-test mathematical skills or motivation. The second aim was to find out whether two play contexts, the group of voluntary players and a second group consisting of students playing at school as a compulsory part of their regular mathematics lessons ( n = 482), differed in game experience, game performance, and cognitive and motivational outcomes. Results . Students from the volunteer group who played had higher pre-test mathematical skills and math interest than those who did not play. Students in this group did not otherwise differ. Compared to students from the volunteer group who played, students in the school group played for longer, completed more tasks, and enjoyed playing the game more. However, their advanced mathematical skills did not improve as much. Conclusion . Motivation did not improve regardless of play context, suggesting serious games should be implemented for their learning content rather than because they are assumed to be motivating.